Nitric oxide as mediator in induction of heat resistance of wheat seedlings by donor of carbon monoxide hemine - Shkliarevskyi, M. A.; Шкляревський, М. А.; Karpets, Yu. V.; Карпець, Ю. В.; Kolupaev, Yu. E.; Колупаєв, Ю. Є.; Lugova, G. A.; Лугова, Г. А.; Bessonova, Valentina; Бессонова, Валентина Петрівна (My University, 2020)
The increase in the heat resistance of seedlings caused by CO donor was levelled by preliminary treatment with the NO scavenger PTIO and the nitrate reductase inhibitor Na2WO4. At the same time, the NO synthase inhibitor aminoguanidine slightly reduced the manifestation of hemin effect on the heat resistance of wheat seedlings. A conclusion has been made about a contribution of nitric oxide, which is synthesized with the participation of nitrate reductase, in the development of CO donor-induced heat resistance of wheat seedlings. Підвищення термостійкості проростків, викликане донором СО, нівелювали попередньою обробкою акцептором NO PTIO та інгібітором нітратредуктази Na2WO4. Водночас інгібітор NO-синтази аміногуанідин дещо зменшував прояв гемінового впливу на термостійкість проростків пшениці. Зроблено висновок про внесок оксиду азоту, який синтезується за участю нітратредуктази, у розвиток донорної СО термостійкості проростків пшениці.
Оксид азоту як медіатор індукції термостійкості проростків пшениці геміном-донором оксиду вуглецю
Keywords: carbon monoxide; окис вуглецю; nitric monoxide; монооксид азоту; nitrate reductase; нітратредуктаза; heat resistance; термостійкість; Triticum aestivum; Triticum aestivum